A Descriptive-Comparative Study Design to Assess Quality of Life in Chronic Venous Disease Using VEINES-QOL/SYM and EQ-5D-5L Questionnaires - Reagan, F. Cabahug; Gina, L. Montalan; Marie, P. Yape, Irma; Maria Cristina, M. Laurenciana (Issues and Developments in Medicine and Medical Research Vol. 2, 2022)
Objective: To determine the efficacy (sensitivity, specificity, and accuracy) of the VeinesQol/Sym with metric statements fewer than the EQ5D in detecting the quality of life of patients with Chronic Venous Disease (CVD) before and after treatment. Introduction Chronic Venous Disease (CVD) commonly presents as varicose veins posing a significant health problem with socio-economic impact in developed countries. Patients with CVD tend to have abnormal ankle-brachial indices and other manageable risk factors for cardiovascular disease. Methods: This is a descriptive-comparative design in collecting the necessary data to arrive at conclusions that respond to the specific questions of the study in 2 private hospitals. The responses gathered from patients through EQ5D and VeinesQol/Sym, before and after they received treatment were utilized in describing and comparing the efficacy of the health questionnaires. Data were further subjected to a comparative analysis to elaborate the efficacy of the VeinesQol/Sym. Results: A total of 114 CVD patients completed the study after excluding 13 patients due to failure to follow up after eight weeks of treatment. The study showed that VeinesQol/Sym and EQ5D has similar efficacy in determining quality of life of CVD patients. However, VeinesQol/Sym has higher accuracy (84.96% vs 76.99%), higher sensitivity (87.85% vs 83.87%), detects greater level of impairment in mobility, anxiety/depression, pain and discomfort, disruptions in usual activity and lower quality of current state of health condition than EQ5D Conclusion: The disease-specific VeinesQol/Sym questionnaire has a higher accuracy and sensitivity rate than the generic EQ-5D-5L. With the responses to the metric statements of the indicators of quality life in both VeinesQol/Sym and EQ5D, VeinesQol/Sym was found to have a greater efficacy in establishing the precise status of quality of life of patients with CVD than the EQ5D.